Hubungan Tingkat Kompetensi Perawat Dengan Penerapan Pendokumentasian Cataan Perkembangan Pasien Terintegrasi Di Ruang Rawat Inap Interna - Talibo, Norman Alfiat; Riu, Silvia Dewi Mayasari; Akili, Magfira (NUTRIX, 2024)
Hypertension is a condition where blood pressure exceeds normal limits and is a serious problem that attacks people of all ages. Observation results showed that there were many patients seeking treatment at the UNAI Clinic who had a history of hypertension. The aim of this study was not to explore the factors associated with the incidence of hypertension in patients seeking treatment at the UNAI clinic. The method used is a quantitative method with an associative (correlation) design. The population is hypertension sufferers with a sample size of 30 people selected based on purposive sampling technique. Data collection was carried out cross-sectionally using a research instrument in the form of a questionnaire adopted from previous research which has been validated and has a Cronbach alpha value of 0.661. For demographic data, descriptive statistical tests were carried out and for relationship tests, Spearman correlation tests were carried out in relation to the data obtained in categorical form. The results of the study showed that there was a significant relationship with the incidence of hypertension, with age (p. value=0.011). However, there was no significant relationship between the incidence of hypertension and other factors, including: family history of hypertension (p. value=0.244), and consumption of salty foods (p. value=0.133), gender (p. value=0.755), level of activity (p. value=0.694), smoking habits (p. value=0.804), coffee drinking habits (p. value=0.463), and body mass index (p. value=0.068). Thus, it can be concluded that the factor related to the incidence of hypertension is age. It is recommended for future researchers to study with a larger sample size, and other factors such as stress, depression, and so on. Catatan perkembangan pasien terintegrasi merupakan hasil kerja kolektif berbagai pihak, seperti dokter, perawat, tenaga kesehatan lain termasuk ahli gizi, serta farmasi. Catatan perkembangan pasien terintegrasi menjelaskan tiga hal yaitu apa yang telah terjadi dengan pasien, apa yang direncanakan untuk pasien dan bagaimana pasien bereaksi terhadap terapi. Tujuan penelitian ini mengidentifikasi hubungan kompetensi perawat dengan pendokumentasian catatan perkembangan pasien terintegrasi (CPPT) di RSU GMIM Pancaran Kasih Manado. Penelitian ini menggunakan metode deskriptif analitik dengan rancangan cross sectional. Sampel penelitian sebanyak 33 responden dengan menggunakan total sampling. Pengumpulan data menggunakan kuesioner dan lembar observasi. Selanjutnya data yang telah dikumpul kemudian dianalisa dengan menggunakan uji statistik Chi-Square dengan tingkat signifikan (α) ≤ 0,05. Berdasarkan data yang diperoleh dari uji Chi-Square terdapat hubungan yang signifikan kompetensi perawat dengan pendokumentasian catatan perkembangan pasien terintegrasi (CPPT) di RSU GMIM Pancaran Kasih Manado, dimana nilai p=0,000. Dimana nilai p lebih kecil dari nilai (α) ≤ 0,05. Kesimpulan penelitian ini adalah ada hubungan kompetensi perawat dengan penerapan pendokumentasian catatan perkembangan pasien terintegrasi (CPPT) di ruang rawat inap interna RSU GMIM Pancaran Kasih Manado. Saran diharapkan dapat menjadi acuan untuk instansi pendidikan sebagai salah satu upaya yang dilaksanakan dalam meningkatkan kualitas kesembuhan pasien.